Human cytomegalovirus RL13 gene transcripts in a clinical strain - Mali Li; Yanping Ma; Yaohua Ji; Rong He; Ying Qi; Zhengrong Sun; Ning Wang; Shuang Gao; Qiang Ruan (Virus Genes, 2011)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Effects of sediment size on transport capacity of overland flow on steep slopes - Guang-Hui Zhang; Li-Li Wang; Ke-Ming Tang; Rong-Ting Luo; X. C. Zhang (Hydrological Sciences Journal, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Analysis of variable sites between two complete South China tiger (Panthera tigris amoyensis) mitochondrial genomes - Wenping Zhang; Bisong Yue; Xiaofang Wang; Xiuyue Zhang; Zhong Xie; Nonglin Liu; Wenyuan Fu; Yaohua Yuan; Daqing Chen; Danghua Fu; Bo Zhao; Yuzhong Yin; et al. (Molecular Biology Reports, 2011)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Single cysteine substitution in Bacillus thuringiensis Cry7Ba1 improves the crystal solubility and produces toxicity to Plutella xylostella larvae - Donghai Peng; Fenshan Wang; Nisha Li; Zhenyu Zhang; Rong Song; Zimin Zhu; Lifang Ruan; Ming Sun (Environmental Microbiology, 2011)
Summary Many Bacillus thuringiensis isolates have no demonstrated toxicity against insects. In this study, a novel holotype crystal protein gene cry7Ba1 was isolated from a ‘non‐insecticidal’ B. thuringiensis strain YBT‐978. The Cry7Ba1 protein showed high toxicity against Plutella xylostella larvae after the crystals were dissolved at pH 12.5, suggesting that the ‘non‐insecticidal’ properties of this protein were due to insolubility in the normal insect midgut pH environment. After the C‐terminal half of Cry7Ba1 was replaced by that of Cry1Ac or Cry1C proteins, the recombinant protein inclusions could be dissolved at pH 9.5, and exhibited high toxicity against P. xylostella larvae. This result proved the insolubility of Cry7Ba1 crystal was determined by the structure of its C‐terminal half. Further, six mutations were constructed by substituting cysteine residues with serine. Solubility studies showed that the crystals from mutants C697S, C834S and C854S could be dissolved at lower pH (10.5, 9.5 and 11.5 respectively). Bioassays showed that crystals from mutant C834S were toxic to P. xylostella larvae. Our discoveries suggest that a single cysteine residue located in the C‐terminal half of the protein determines the solubility and toxicity of some nontoxic crystal proteins. This study provides a strategy to isolate novel insecticidal crystal protein genes from ‘non‐insecticidal’ B. thuringiensis strains.

Fluorescence in situ hybridization on plant extended chromatin DNA fibers for single-copy and repetitive DNA sequences - Kun Yang; Hecui Zhang; Richard Converse; Yong Wang; Xiaoying Rong; Zhigang Wu; Bing Luo; Liyan Xue; Li Jian; Liquan Zhu; Xiaojia Wang (Plant Cell Reports, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Trigonella arcuata-associated rhizobia—an Ensifer (Sinorhizobium) meliloti population adapted to a desert environment - Yu Rong He; Jing Yu Wang; En Tao Wang; Gu Feng; Yue Li Chang; Xin Hua Sui; Wen Xin Chen (Plant and Soil, 2011)

Cloning and functions analysis of a pyruvate dehydrogenase kinase in Brassica napus - Rong-Jun Li; Zhi-Yong Hu; Hua-Shan Zhang; Gao-Miao Zhan; Han-Zhong Wang; Wei Hua (Plant Cell Reports, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Synthesis, Characterization, DNA Binding Properties and Antioxidant Activity of Ln(III) Complexes with Schiff Base Ligand Derived from 3-Carbaldehyde Chromone and Aminophenazone - Yong Li; Zheng-yin Yang; Tian-rong Li; Zeng-chen Liu; Bao-dui Wang (Journal of Fluorescence, 2011)

Expansin-regulated cell elongation is involved in the drought tolerance in wheat - Mei-rong Zhao; Feng Li; Ying Fang; Qiang Gao; Wei Wang (Protoplasma, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Mineral status and mechanical properties of cancellous bone exposed to hydrogen peroxide for various time periods - Dan Li; Long Bi; Guolin Meng; Jun Wang; Rong Lv; Min Liu; Jian Liu; Yunyu Hu (Cell and Tissue Banking, 2011)

Comparison of DNA extraction methods for the PCR-single-strand-conformation polymorphism analysis of kefir - Shu-Jun Chen; Qing Wang; Jian-Rong Han; Yu Wang; Zhi-Wei Li (World Journal of Microbiology and Biotechnology, 2011)

Serum complement C3 has a stronger association with insulin resistance than high sensitive C-reactive protein in non-diabetic Chinese - Bangqiong Wang; Qifu Li; Yuanjuan Jiang; Zhoujun Liu; Li Zhong; Rong Luo; Qingfeng Cheng; Hua Qing (Inflammation Research, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.